Influence of Streptococcus mitis and Streptococcus sanguinis on virulence of Candida albicans: in vitro and in vivo studies - do Rosário Palma, Ana Luiza [UNESP]; Domingues, Nádia [UNESP]; de Barros, Patrícia Pimentel [UNESP]; Brito, Graziella Nuernberg Back [UNESP]; Jorge, Antônio Olavo Cardoso [UNESP] (Springer Nature, 2019)
The aim was to evaluate in vitro possible interactions, gene expression, and biofilm formation in species of Candida albicans, Streptococcus mitis, and Streptococcus sanguinis and their in vivo pathogenicity. The in vitro analysis evaluated the effects of S. mitis and S. sanguinis on C. albicans’s biofilm formation by CFU count, filamentation capacity, and adhesion (ALS1, ALS3, HWP1) and transcriptional regulatory gene (BCR1, CPH1, EFG1) expression. In vivo studies evaluated the pathogenicity of the interaction of the microorganisms on Galleria mellonella, with analyses of the CFU per milliliter count and filamentation. In vitro results indicated that there was an observed decrease in CFU (79.4–71.5%) in multi-species biofilms. The interaction with S. mitis inhibited filamentation, which seems to increase its virulence factor with over-expression of genes ALS1, ALS3, and HWP1 as well the interaction with S. sanguinis as ALS3 and HWP1. S. mitis upregulated BRC1, CPH1, and EFG1. The histological images of in vivo study indicate an increase in the filamentation of C. albicans when in interaction with the other species. It was concluded that S. mitis interaction suggests increased virulence factors of C. albicans, with periods of lower virulence and proto-cooperation in the interaction with S. sanguinis.